Implementasi Quantitative Strategic Planning Matrix Dalam Menentukan Strategi Penjualan Usaha Kuliner - Tanisri, Roberta H. A.; Putra, Bhakti Dwi; Suminar, Ratna; Apriyani, Apriyani (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2023)
The Ayam Bakar 'Mat Negro' culinary business has been established since 2018. Having four employees in running the business, the business owner experienced a decrease in sales turnover in 2021. The research focuses on increasing sales through the application of the right marketing strategy in marketing the business products of this Ayam Bakar 'Mat Negro' culinary business. The approach used is the Quantitative Strategic Planning Matrix (QSPM) method. The preparation process of the method uses the IFAS matrix, EFAS matrix, and SWOT diagram. There are three alternative strategies, namely providing special discount prices if there are large orders, opening new branches in locations close to office areas, and maintaining the quality of the grilled chicken flavor. The main priority that can be done by business owners is to implement strategies to maintain the quality and taste of grilled chicken.